PENGARUH PEMBERIAN REWARD TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN IPS KELAS VI SDIT BPMAA PEKANBARU - Suhudi, Suhudi; Aramudin, Aramudin; M. Fikri Hamdani; Risnawati, Risnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine the effect of giving rewards on students' learning motivation in social studies learning in class VI SDIT BPMAA. The research method used is quantitative with an experimental design. The research subjects were class V students at SDIT BPMAA, consisting of two groups. Data was collected through learning motivation questionnaires and learning outcomes tests which included social studies material. Data analysis was carried out using the Wilcoxon test to compare the level of learning motivation between the experimental group and the control group. The results of the study showed that there was a significant difference in motivation to learn social studies between students who were given rewards and those who were not. Students who were given rewards showed a significant increase in their learning motivation compared to students who were not given rewards. By looking at the results of the SPSS test which uses the Wilcoxon test, where the sig value is smaller than the value 0.005 or 0.00 < 0.05, it can be said that reard training is very influential in increasing students' learning motivation abilities. The conclusion of this research is that giving rewards has a positive influence on the learning motivation and social studies learning outcomes of class V students at SDIT BPMAA. Therefore, the strategy of giving rewards can be considered as a method to increase student motivation and learning outcomes in social studies subjects, written in a maximum of 250 words describing the problem, research objectives, methodology and results obtained.